Implementation of The Waterfall Model on Android-Based Travel Ticket Booking Applications - Ganda Yoga Swara; Indra Warman; Dede Wira Trise Putra (Journal of Information System, Informatics and Computing, 2022)
The purpose of this research is to design and develop an android-based information system for business travel, especially in the process of marketing, ordering, payment, departure. Changing the process that had been done manually to be more systematic and structured in order to be able to present information to consumers in real-time. Research with this observation method uses the waterfall model in developing its information system. The results of this study can work 100% after black box testing. In addition, the results of data analysis of user satisfaction using a Likert scale and Kaplan and Norton analysis obtained the average user satisfaction by raising 4.44, meaning that users are very satisfied with this information system.